Konsep al-Falah dalam Islam dan Implementasinya dalam Ekonomi - Khaerul Aqbar; Azwar Iskandar; Akhmad Hanafi Dain Yunta (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
The study aims to: (1) know the epistemology and concept of al-fala>h in Islamic perspective; (2) know the implementation of al-fala>h concept in micro and macroeconomic. The study uses a qualitative-descriptive approach with library research technique. The results showed that in Islamic epirstemology, al- al-fala>h defined as all forms of happiness, luck, success and prosperity that is perceived by a person, both born and inner, which it can be feeled in the world and in the hereafter, from all sides and dimensions (comprehensive) in all aspects of life. The concept of al-fala>h demands a muslim to be oriented to the community in every activity, where the hereafter becomes the ultimate goal of the process in the world continuously, while the material facilities in the world can be maximised to maximize the implementation of worship to God more perfectly. Al-fala>h is a multidimensional concept that has implications on the aspects of individual behaviour (micro) and collective behavior (macro), namely survival, freedom of desire, strength and self-esteem and spirituality.